Fabrication of Na and K based MnO2 nanocomposites for supercapacitive applications - Vashisth, Priyanka; Sharma, Aditya; Nasit, Manas; Singh, Jitendra Pal; Anjali; Varshney, Mayora; Kumar, Shalendra; Won, S. O.; Shin, H. J. (Cell Press, 2024)
alpha-Na0.5Mn0.93O2@Na0.91MnO2 (NaMnO) and K0.48Mn1.94O5@Na0.91MnO2 (KNaMnO) nanocomposites have been synthesized using solid-state reaction method. FESEM results convey the formation of column-shaped morphology. FTIR exhibited a shift in the vibration frequency upon potassium loading. Cyclic voltammetric curves are scanned (0 V-0.8 V) at different scan rates (5 mV/s to 100 mV/s) in 1M KOH electrolyte. Galvanostatic charge-discharge characteristics, for different current densities, have shown non-linear or pseudocapacitive characteristics of the prepared electrodes. High specific capacitance of similar to 361 F/g and similar to 143 F/g, at a current density of 1A/g, has been achieved for KNaMnO and NaMnO samples, respectively. KNaMnO sample exhibited higher capacitive retention (116 %), up to 2000 cycles, and obeys lower series resistance, charge transfer resistance, and Warburg impedance parameters, thus, convey higher efficiency of this compound for supercapacitor applications.